Torticollis as the Main Presentation in a Child with Russell-Silver Syndrome: A Case Report - Mohsen Javadzadeh; Hedieh Saneifard; Amir Hossein Hosseini (Case Reports in Pediatrics, 2012)
Russell-Silver syndrome is a genetic disorder the inheritance pattern of which is mostly sporadic. Some of the features of the syndrome are present at birth, and others appear in later years. The main clinical features include low birth weight, poor growth postnatally, short height, and discrepancies in size between the two sides of the body Abu-Amera et al. (2008), Binder et al. (2011). There is no statistical significant difference in prevalence between males and females. We report a case of Russell-Silver syndrome with intrauterine and postnatal growth retardation, triangular face, and body asymmetry, in addition to torticollis as a novel manifestation. In neck sonography, we found asymmetry of sternocleidomastoid muscles. In conclusion, we describe torticollis as a presentation of Russell-Silver syndrome.